Sifat-Sifat Da'i Dalam Al-Qur'an (Kajian Surah Ali' Imran Ayat 159) - Fauziah, Mira (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2020)
Daâ€Ÿi is a figure who should have good qualities because he is a role model for mad'u. This research is a library research, qualitative approach and content analysis method. Researchers determine QS. Ali Imran 3: 159 as the object of study. This verse describes the praiseworthy qualities of the Prophet Muhammad. when facing friends in the Uhud war. In a precarious situation the Prophet remained gentle, forgiving, had a strong determination and put his trust in Allah SWT. The da'i should be able to imitate the nature of the Prophet as described in the verse.Â